Seasonal Distribution of Petroleum Hydrocarbons in Imported Rainbow Trout Organs - Ali M. Galo; Rajaa N. Alyassein; Ghassan A. Al-Najare; Ali T. Yaseen (Indonesian Journal on Health Science and Medicine, 2026)
General background: Petroleum hydrocarbons are persistent aquatic contaminants capable of bioaccumulation in fish tissues, posing ecological and public health concerns. Specific background: Rainbow trout (Oncorhynchus mykiss) are widely consumed in Basra Governorate and are sensitive bioindicators of hydrocarbon pollution. Knowledge gap: Limited information exists on seasonal and organ-specific distribution of total petroleum hydrocarbons (TPHs) in imported trout sold in local markets. Aims: This study quantified seasonal TPH concentrations in selected organs of spotted and pink O. mykiss obtained from Basra markets. Results: TPH levels varied significantly among organs and seasons (P≤0.05), with the highest concentrations consistently detected in the liver, particularly during spring (up to 2.88 µg/g dry weight), while muscles and gonads showed the lowest levels (as low as 0.01 µg/g dry weight). Novelty: The study provides market-based evidence of differential TPH accumulation patterns in imported trout, rather than wild-caught populations, highlighting seasonal trends linked to biological and environmental processes. Implications: Although muscle tissues showed lower contamination, detectable TPHs indicate potential long-term bioaccumulation risks, underscoring the need for routine monitoring of imported fish to safeguard consumer health. Highlights: Liver consistently exhibited the highest TPH accumulation across seasons. Spring recorded peak TPH concentrations in both trout varieties. Edible muscle tissues contained lower but detectable TPH levels. Keywords: Total Petroleum Hydrocarbons; Rainbow Trout; Fish Organs; Seasonal Variation; Bioaccumulation